FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PETANI KELAPA SAWIT RAKYAT BERPARTISIPASI DALAM SERTIFIKASI PRODUK DI KABUPATEN KAMPAR - Rizka Emilia; Sakti Hutabarat; Arifudin Arifudin (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
Oil  palm  product  certification  consists  of  the  Roundtable  of  Sustainable Palm  Oil  (RSPO)  and  the  Indonesian  Sustainable  Palm  Oil  (ISPO).  RSPO certification is a voluntary certificate that must be met by oil palm mills to sell their products in international market. ISPO is a mandatory certificate that must be comply by grower and miller which operate their bisnis in Indonesia. A number of principles and criteria must be comply by smallholders  to obtain RSPO certificate. The objective of  this study  is to  analyse  farmer  perception  and  factors  that  influence  smallholder participation  in  certification  in  Kampar  Regency.  The  population  of  this  study  are scheme  smallholders  (NES/KKPA)  and  independent  smallholders.  This  study  use Summated  Likert  scale  rating  to  evaluate  farmers’  perception  and  binary  logistic regression  to assess smallholders participation. The results show that certification is very important while it is important for independent smallholders. Education and land size  are  factors  that  influnce  scheme  smallholders  in  participating  in  certification while eduction, land size and job are factors that influence independent smallholders.